Comparison of ROX Index and Surfactant Protein-D with HFNC Outcome in COVID-19 Patients - Rozi, Achmad Syamsufandi; Parsama Putra , Ngakan Putu; Setyawan, Ungky Agus; Listyoko, Aditya Sri (RSUP Dr. Kariadi, 2023)
Background: In COVID-19, severe clinical deterioration can lead to respiratory distress. High Flow Nasal Cannula (HFNC) is an oxygenation treatment recommended in severe COVID-19 patients, with various studies showing decreased recovery time and intensive care needed. However, instruments to predict HNFC outcomes, specifically in COVID-19, are not yet widely studied. ROX index is a practical instrument proven effective in predicting HFNC outcome in pneumonia while showing high variabilities of optimum time of assessments and cut-off values in COVID-19. Surfactant Protein-D (SP-D) is an alveolar protein showing potential as a biomarker in acute lung injury and respiratory distress. In this study, we analyzed ROX index and SP-D potential as HFNC outcome predictors in COVID-19 patients. Methods: This prospective study recruited severe and critical COVID-19 patients treated with HFNC. Patient characteristics, laboratory values including initial serum SP-D values, and ROX index were recorded. Significant differences were analyzed using Chi-Square and Mann-Whitney tests. Receiver operating characteristic (ROC) analysis was used to determine HFNC outcome predictive abilities of ROX index and serum SP-D. Result: 31 subjects with successful HFNC outcomes in 19 subjects and failed HFNC outcomes in 12 subjects were included in this study. ROX index and SP-D value were significantly higher in subjects with successful HFNC compared to failed HFNC (p < 0.05). ROX index at 6, 12, and 24 hours showed good HFNC outcome predictive ability (AUC > 0.7, p < 0.05). Conclusion: Successful HFNC outcome in COVID-19 was significantly related to higher ROX index and serum SP-D values. ROX index also showed good potential as an HFNC outcome predictor in COVID-19 patients.